Pendampingan Asesmen Pembelajaran Dalam Implementasi Kurikulum Merdeka Pada SMAN 13 Takalar - Harry Yulianto; Iryani Iryani (To Maega : Jurnal Pengabdian Masyarakat, 2023)
The learning assessment on implementing the independent curriculum aims to determine student learning outcomes' needs, developments, and achievements. This activity aims to assist teachers at SMAN 13 Takalar regarding learning assessments in implementing the independent curriculum. The methods of implementing the activities are training and advocacy. The training method uses lecture, discussion, and practice techniques. The advocacy method uses presentation, dialogue, and negotiation techniques. The analysis technique used is descriptive statistics. The results of the activities indicated: 1) the training participants had a high level of ability to absorb knowledge and apply learning assessments, 2) the problems faced by the participants could find solutions to solve them, and 3) the advocacy results provided enlightenment for stakeholders at SMAN 13 Takalar in implementing assessment policies according to the conditions of the academic unit. The next activity is the recommendation to hold training regularly and optimize the role of the community of practitioners in schools to share good practices.